Rediscovery of presumed extinct Hypoestes lanata (Acanthaceae), a little known endemic species from the Western Ghats of Maharashtra, India - Raskar, Shivaji V.; Patale, Madhukar W.; Salunkhe, Chandrakant B.; Bramhadande, Sneha P.; Nandikar, Mayur D. (Phytotaxa, 2022)
Hypoestes lanata Dalzell (Acanthaceae), a narrow endemic species is rediscovered after a lapse of 80 years from the type locality, i.e. north Konkan, Maharashtra, India. A distribution note on the genus Hypoestes, detailed description of the species, illustration, distribution map, threat status and photographs are provided to facilitate identification. As multiple specimens are associated with H. lanata, a note on the original material is provided and lectotype designated.